# No idea how to do this

• May 8th 2008, 02:16 PM
lax600
No idea how to do this
$(x - y)^2 + 13(x - y) + 42$

Please someone help me or something. I have no idea how to do this at all.
Like what do I do when its $(x - y)^2$?
• May 8th 2008, 02:30 PM
icemanfan
Quote:

Originally Posted by lax600
$(x - y)^2 + 13(x - y) + 42$

Please someone help me or something. I have no idea how to do this at all.
Like what do I do when its $(x - y)^2$?

I'm guessing you want to expand this.

$(x - y)^2 = x^2 - 2xy + y^2$, for starters.
• May 8th 2008, 02:31 PM
lax600
I need to factor it... so I still expand it?
• May 8th 2008, 02:34 PM
icemanfan
$(x - y)^2 + 13(x - y) + 42$ is about as factored as it gets. One thing you can do:

$(x - y + 13)(x - y) + 42$
• May 8th 2008, 02:51 PM
lax600
I just asked my dad how to do this and he replys:

$(x - y)^2 - 13(x - y) + 42$

if $(x - y)^2 - 14(x - y) + 49$

$(x - y)^2 - 2*7*(x - y) + 7^2$

a = $(x - y)^2$
b = $7$

$(x - y)^2 - 13(x - y) + 42
= [(x - y)^2 - 14(x - y) + 49]
={[(x - y) - 7]^2 + [(x - y) - 7]}$

$=(x - y -7){x - y - 7}
=(x - y - 7)(x - y - 6)$
• May 8th 2008, 02:58 PM
icemanfan
Quote:

Originally Posted by lax600
I just asked my dad how to do this and he replys:

$(x - y)^2 - 13(x - y) + 42$

if $(x - y)^2 - 14(x - y) + 49$

$(x - y)^2 - 2*7*(x - y) + 7^2$

a = $(x - y)^2$
b = $7$

$(x - y)^2 - 13(x - y) + 42
= [(x - y)^2 - 14(x - y) + 49]
={[(x - y) - 7]^2 + [(x - y) - 7]}$

$=(x - y -7){x - y - 7}
=(x - y - 7)(x - y - 6)$

yeah, that's right. Just substitute $t = x-y$ and you have $t^2 - 13t + 42$ which easily factors to $(t - 6)(t - 7)$. I should have been thinking along those lines.
• May 8th 2008, 03:01 PM
lax600
oh